2020
DOI: 10.3390/pharmaceutics12111045
|View full text |Cite
|
Sign up to set email alerts
|

CancerGram: An Effective Classifier for Differentiating Anticancer from Antimicrobial Peptides

Abstract: Antimicrobial peptides (AMPs) constitute a diverse group of bioactive molecules that provide multicellular organisms with protection against microorganisms, and microorganisms with weaponry for competition. Some AMPs can target cancer cells; thus, they are called anticancer peptides (ACPs). Due to their small size, positive charge, hydrophobicity and amphipathicity, AMPs and ACPs interact with negatively charged components of biological membranes. AMPs preferentially permeabilize microbial membranes, but ACPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 62 publications
(87 reference statements)
0
13
1
Order By: Relevance
“…While, hydrophobic Leu and Ile constituted 19% of the ACP sequences [48].Like AMPs, both positive net charge and hydrophobicity is needed for the functioning of ACPs, however, the anticancer activity does not improve by increasing net charge and hydrophobicity beyond a certain limit. A reciprocity between these two factors are important for the proper functioning ACPs [49].Our finding showed Cys, Gly, and Pro as frequently occurring amino acids The amino acid distribution pattern was aberrant considering the reports made by previous studies but a recent study backed Gly and Cys as abundant amino acids in ACPs [50].…”
Section: Discussioncontrasting
confidence: 44%
“…While, hydrophobic Leu and Ile constituted 19% of the ACP sequences [48].Like AMPs, both positive net charge and hydrophobicity is needed for the functioning of ACPs, however, the anticancer activity does not improve by increasing net charge and hydrophobicity beyond a certain limit. A reciprocity between these two factors are important for the proper functioning ACPs [49].Our finding showed Cys, Gly, and Pro as frequently occurring amino acids The amino acid distribution pattern was aberrant considering the reports made by previous studies but a recent study backed Gly and Cys as abundant amino acids in ACPs [50].…”
Section: Discussioncontrasting
confidence: 44%
“…In the ACPs datasets, KNN and RF of the classical algorithm are excellent, while AdaBoostM1, Bagging, Vote and Stacking of the ensemble algorithm show high accuracy. Compared with the previous model prediction methods for ACPs [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], features were extracted based on the 3D structure of peptides for the first time, which can be used as a supplementary method for the prediction of ACPs. The extraction of features from the 3D structure of peptides can better reflect the state of peptides in organisms and analyze the properties of peptides from different perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Then, Hajisharififi et al [ 9 ] developed a model of SVM based on Chou’s pseudo-amino acid composition (PseAAC) and local alignment kernel. After that, researchers have established many predictors, for example, ACPP [ 10 ], iACP [ 11 ], MLACP [ 12 ], iACP-GAEnsC [ 13 ], ACPred-FL [ 14 ], SAP [ 15 ], TargetACP [ 16 ], ACPred [ 17 ], mACPpred [ 18 ], ACPred-Fuse [ 19 ], PTPD [ 20 ], ACP-DL [ 21 ], PEPred-suite [ 22 ], AntiCP 2.0 [ 23 ], CancerGram [ 24 ], DeepACP [ 25 ] and ENNAACT [ 26 ], most of them adopt diverse feature extraction methods combined with various machine learning algorithms. All of the above predictors performed well in distinguishing between ACPs and non-ACPs.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the drugs maybe designed specifically. For instance, Burdukiewicz et al have showed a robust computational tool, CancerGram helping researchers to find appropriate anticancer peptides to target mitochondria in the cancer cells [12].…”
mentioning
confidence: 99%
“…In conclusion, this Special Issue underlines importance of mitochondria in pathophysiological situation such as: genetic disorders [1,2], cardiovascular diseases [3,4], inflammation [5] and cancer [6][7][8][9][10]. Indicates new tools to selective target mitochondria in order to: rescue aberrant cell phenotype, change cell metabolism or induces mitochondria dependent cell death [1][2][3][4][5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%